The crystal structure of 3-(carboxymethyl)-1-ethenyl-1H-imidazol-3-ium chloride, C7H9N2O2Cl - Song Wenqi; Yang Miaoxiu; Qian Liwei; Miao Zongcheng (Zeitschrift für Kristallographie - New Crystal Structures)
C7H9N2O2Cl, orthorhombic, P212121 (no. 19), a = 4.6321(3) Å, b = 7.5132(4) Å, c = 24.7605(14) Å, V = 861.71(9) Å3, Z = 4, Rgt(F) = 0.0257, wRref(F2) = 0.0653, T = 193 K.